2015
DOI: 10.15288/jsad.2015.76.569
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between African-American and European- American Women in the Association of Childhood Sexual Abuse With Initiation of Marijuana Use and Progression to Problem Use

Abstract: ABSTRACT. Objective: Childhood sexual abuse (CSA) is associated with elevated risk of early marijuana use and cannabis use disorder (CUD). Both the prevalence of CSA and the course of marijuana use differ between African Americans and European Americans. The current study aimed to determine whether these differences manifest in racial/ ethnic distinctions in the association of CSA with early and problem use of marijuana. Method: Data were derived from female participants in a female twin study and a high-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
5
0
3
Order By: Relevance
“…La búsqueda en las bases de datos incluyó todos los tipos de violencia, no obstante, únicamente seis artículos informaron las frecuencias de casos de individuos con exposición a la violencia (abuso sexual, abuso físico, y ser testigo de violencia) durante la infancia y uso o abuso de cannabis en la adolescencia. Cinco estudios fueron diseños de cohorte, pero con evaluaciones transversales efectuadas en periodos concretos de la vida de los participantes (Dubowitz et al, 2016;Duncan et al, 2008;Fergusson y Horwood, 1998;Fergusson y Lynskey, 1997;Sartor et al, 2015), mientras que el estudio de Kilpatrick et al (2000) fue desarrollado a partir de una muestra probabilística derivada de la National Household Survey (Encuesta Nacional en Hogares). Los estudios conducidos por Fergusson y Horwood (1998) y Fergusson y Lynskey (1997), fueron desarrollados a partir de la misma muestra; sin embargo, para los fines de esta revisión sistemática, los datos fueron tratados de forma independiente ya que son resultado de diferentes tipos de violencia (Tabla 1).…”
Section: Descripción De Los Estudiosunclassified
See 2 more Smart Citations
“…La búsqueda en las bases de datos incluyó todos los tipos de violencia, no obstante, únicamente seis artículos informaron las frecuencias de casos de individuos con exposición a la violencia (abuso sexual, abuso físico, y ser testigo de violencia) durante la infancia y uso o abuso de cannabis en la adolescencia. Cinco estudios fueron diseños de cohorte, pero con evaluaciones transversales efectuadas en periodos concretos de la vida de los participantes (Dubowitz et al, 2016;Duncan et al, 2008;Fergusson y Horwood, 1998;Fergusson y Lynskey, 1997;Sartor et al, 2015), mientras que el estudio de Kilpatrick et al (2000) fue desarrollado a partir de una muestra probabilística derivada de la National Household Survey (Encuesta Nacional en Hogares). Los estudios conducidos por Fergusson y Horwood (1998) y Fergusson y Lynskey (1997), fueron desarrollados a partir de la misma muestra; sin embargo, para los fines de esta revisión sistemática, los datos fueron tratados de forma independiente ya que son resultado de diferentes tipos de violencia (Tabla 1).…”
Section: Descripción De Los Estudiosunclassified
“…Por su parte, Dubowitz et al (2016) recopilaron datos a partir de varias fuentes: informes de los Servicios de Protección al Menor, y posteriormente, de entrevistas a los padres y los niños. Un estudio recopiló la información mediante una entrevista telefónica diseñada por los autores (Kilpatrick et al, 2000), mientras que dos estudios investigaron vía telefónica las características del abuso con la Semi-structured Assessment for the Genetics of Alcoholism (SSAGA; Evaluación Semiestructurada para el Estudio de la Heredabilidad del Alcoholismo) (Duncan et al, 2008;Sartor et al, 2015) (Tabla 2). Por lo tanto, los estudios analizados en esta revisión reportaron una variedad de métodos para la obtención de la información relativa a los diferentes tipos de violencia.…”
Section: Descripción De Los Estudiosunclassified
See 1 more Smart Citation
“…parental substance use, parental violence) have been shown to increase the risk for substance use disorders (SUD) and comorbid psychopathology (McLaughlin et al 2010). However, recent studies have shown that these exposures are not as strongly associated with SUD among African-Americans (AAs; Sartor et al 2015; Werner et al 2016 a , b ) and that associations may differ by gender (Smith et al 2010; Schiff et al 2014). These findings, together with known differences in rates of exposure to childhood trauma (Roberts et al 2011; Sumner et al 2015) and adult SUD (Grant et al 2015; Chou et al 2016; Hasin et al 2016), warrant further research investigating potential racial/ethnic and gender heterogeneity in the relation of childhood trauma and adult SUD.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited research directly examining the association of race in the relationship between trauma exposure and RSB, existing knowledge of racial differences in RSB, STI rates, and trauma exposure highlight the heterogeneity of the adolescent and young adult female population. Furthermore, discrepancies between Black and White women in the trauma-related etiology of other risky behaviors such as alcohol and cannabis misuse have been reported (Sartor et al, 2015; Werner et al, 2016; Werner, Sartor, et al, 2016). Finally, there are marked socio-ecological differences between and within White and Black communities across the United States and subsequent implications for disparities in health and mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%